Development of Problem-Based Learning (PBL) Chemistry Modules to Provide Students’ Numeracy-Literacy Skills in Materials of Colligative Property Solutions - Tutus Martiana; Wardani, Sri; Nuswowati, Murbangun (Chemistry in Education, 2025)
Education is one aspect that needs to be improved in building quality Human Resources (HR). Life in the 21st century requires important skills that must be mastered by everyone, especially students, in order to face existing challenges. Numeracy literacy is part of the basic literacy in 21st-century skills that must be possessed. This study aims to develop a PBL-based chemistry learning module to equip students with numeracy literacy skills on the topic of colligative properties of solutions. The difference lies in the content of the developed module, the material, and the abilities studied, where no previous similar research has examined the development of a PBL-based chemistry learning module to equip students with numeracy literacy skills on the topic of colligative properties of solutions. In this module, PBL syntax is used as a guide in the implementation of learning (material descriptions, case studies, and formative tests of numeracy literacy), and numeracy literacy becomes a reference for the content to be included in the module. The method used in this study is the Research and Development (R&D) method. The development research conducted refers to the 4D model according to Thiagarajan, which consists of Define, Design, Development, and Dissemination. A small-scale trial involved 8 students from class XII MIPA with the criteria of having studied the colligative properties of solutions. A large-scale trial involved 36 students of class XII-E as the experimental class and 36 students of class XII-D as the control class, selected using a purposive sampling technique with consideration from the teacher. The results are: 1) the module is declared feasible with the results of media and material validity of 100% (very valid) and the results of readability and implementation getting a percentage of 92% (very good); 2) the module is declared quite effective with classical learning completion in class XII-E of 50%; and 3) the module received a positive response from teachers and students with a teacher response value of 93% and a student response value of 78%. Based on these results, it can be concluded that the PBL-based chemistry learning module is feasible and quite effective for use in chemistry learning, especially the colligative properties of solutions.